2012
DOI: 10.5301/hip.2012.9059
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Cost of Treating Early Dislocation following Hip Arthroplasty

Abstract: Dislocation is a frequent and costly complication of hip arthroplasty. The purpose of this study was to assess the financial impact on the treating institution of this complication in patients with primary hemiarthroplasty (HA), total hip arthroplasty (THA) and revision surgery (RTHA). Between October 2001 and August 2009, 2014 consecutive hip arthroplasties were performed at our institution, of which 87 (18 HA, 44 THA and 25 RTHA) dislocated within 6 weeks of the primary operation. The average cost of treatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 20 publications
1
24
2
3
Order By: Relevance
“…[2][3][4][5] Such findings have implications for the centralization of delivery of arthroplasty, 6 particularly as these complications are associated with considerable morbidity and increased healthcare costs. [7][8][9][10] There is, however, a lack of consensus around what constitutes a "low" annual volume, with definitions ranging from less than six to less than 52 procedures a year. [11][12][13] The lack of a consistent definition is a reflection of the fact that volume thresholds have typically been created to ensure an even distribution of patients across volume categories.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Such findings have implications for the centralization of delivery of arthroplasty, 6 particularly as these complications are associated with considerable morbidity and increased healthcare costs. [7][8][9][10] There is, however, a lack of consensus around what constitutes a "low" annual volume, with definitions ranging from less than six to less than 52 procedures a year. [11][12][13] The lack of a consistent definition is a reflection of the fact that volume thresholds have typically been created to ensure an even distribution of patients across volume categories.…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation of these findings is important. In addition to the significant morbidity associated with these complications (16,17), if joint replacement recipients with RA are found to be at greater risk of surgical complications, this may have implications for surgical decision-making. The current study sought to overcome the limitations of prior studies.…”
mentioning
confidence: 99%
“…2 DaPalma et al analysed the financial impact of complications following hip arthroplasty and found the additional cost of a dislocation within six weeks of surgery is 342% of the primary cost. 3 …”
Section: Introductionmentioning
confidence: 99%